Effect of commercial guar meal (CGM) on the performance and nutrient utilization in broilers - RAO, M HANUMANTH; REDD, V RAVINDER; RAO, S V RAMA; KUMAR, M SHASHI; KUMARI, N NALINI; SRINIVAS, GURRAM; RAGHUNANDHAN, T (The Indian Journal of Animal Sciences, 2019)
A biological trial was undertaken to study the effect of inclusion of graded levels of commercial guar meal (CGM) in diet on the performance and nutrient digestibility in commercial broiler chickens. A total of 350 oneday- old broiler male chicks (Cobb 400) were reared on wire floor electrically heated battery brooders. The chicks were randomly divided into 7 groups. Each treatment had 10 replicates of 5 chicks each. All the groups received iso-nitrogenous and iso-caloric diets. First group was fed maize-SBM; 2nd, 3rd and 4th groups were fed control diet during pre-starter phase (1–14 days), later (starter and finisher phase) CGM was incorporated at 6, 12 and 18% respectively, replacing SBM. In rest 3 groups (5th, 6th and 7th), CGM was incorporated at 6% during pre-starter phase followed by (starter and finisher phase) incorporation of CGM at 6, 12 and 18% respectively. The results showed that body weight gain (BWG) was significantly better at 6% CGM inclusion and depressed at 12 and 18% CGM. There was no significant effect of non-inclusion of CGM in juvenile phase on BWG; though feed intake did not differ significantly by CGM inclusion but FCR was significantly higher at all inclusion levels of CGM (6, 12 and 18%). The slaughter parameters, nutrient digestibility, serum parameters did not differ significantly. It can be concluded that CGM could be incorporated up to 6% (60 g/kg diet) in broiler diets without affecting growth performance, nutrient utilization and slaughter variables.